A Diselenide Turn‐On Fluorescent Probe for the Detection of Thioredoxin Reductase. (17th June 2020) - Mafireyi, Tendai J.; Laws, Madeleine; Bassett, John W.; Cassidy, Pamela B.; Escobedo, Jorge O.; Strongin, Robert M.
Abstract: We report the first diselenide‐based probe for the selective detection of thioredoxin reductase (TrxR), an enzyme commonly overexpressed in melanomas. The probe design involves conjugation of a seminaphthorhodafluor dye with a diselenide moiety. TrxR reduces the diselenide bond, triggering a fluorescence turn‐on response of the probe. Kinetic studies reveal favorable binding of the probe with TrxR with a Michaelis–Menten constant ( K m ) of 15.89 μm . Computational docking simulations predict a greater binding affinity to the TrxR active site in comparison to its disulfide analogue. In vitro imaging studies further confirmed the diselenide probe exhibited improved signaling of TrxR activity compared to the disulfide analogue. Abstract : A reductive approach : A diselenide‐based probe for the detection of thioredoxin reductase 1 (TrxR1) was designed and synthesized. The non‐fluorescent probe switched on in the presence of TrxR1 and had minimal interference from other biological reducing species. The diselenide probe was successfully used in imaging TrxR1 in human lung cancer cells and showed greater fluorescence compared to a disulfide‐based analogue.